A historical study of industrial ethnicity in urban colonial Zimbabwe and its contemporary transitions : the case of African Harare, c. 1890-1980 - Manganga, Kudakwashe (Stellenbosch : Stellenbosch University, 2014)
Thesis (PhD)--Stellenbosch University, 2014.